Pendampingan Penggunaan Mesin Pengaduk Adonan Kue untuk Mengurangi Waktu dan Biaya Produksi Bakpia di Industri Rumahan - Kartinasari Ayuhikmatin Sekarjati; Angger Bagus Prasetiyo (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2024)
This community service was motivated by the need for cake and bakpia producers to improve efficiency and consistency in the dough mixing process previously done manually. This service aims to introduce and train the use of dough-mixing machines that can speed up the production process and improve product quality. The community service methods used include problem identification, machine design and manufacture, socialization, and training in the use and maintenance of the machine to 12 participants, consisting of 2 business owners and 10 employees. This activity also includes a live demonstration to ensure participants understand how to operate the machine. The results of the community service show that the dough mixing time has decreased from 30-45 minutes to 10-15 minutes, with an increase in participants' understanding of machine operation and maintenance reaching 100%. Participants' enthusiasm and confidence in using the machine also increased, showing great potential to increase their productivity and business competitiveness in the market.